ISTIQAMAH TERHADAP SYARI'AT AGAMA (Studi Psikologi Agama) - Burdjani As. (Pascasarjana UIN ANTASARI Banjarmasin, 2007)
Ltiqdhrh k dne's .ondinon oi ad effon tlr dtibntely keep folowing thc a) of relsion s guided bt' AIah SwI. Literaly, this word mcms srraight, detemi,ed, dd consisrent.',a religious pe6oq, someone musr be obedimt to fie law ot l!1s religion and folow the way guided by Allah. htiquah is tne otposne olhi?o.nsy. - h?ocri p^on is tror consisrenr berwee. vhat is in hi3 hcart. his vords, and his acts, likes ro lie, never Leeps the promis, od betays odefs tn,. Lr?22,.4 is able to prevent a peaon from dohg e' especidly ddiat io .Ul2h aqcr hc acknoNledges his fdrlt. A personsao is isiiqaruh tovards laws of .elgon 6 honest. nght, md ncntally healthy. Psychologlcaly, a person who is ncrtal hcaldT has m iliq, to djust with hioself. othd people, md rhe slfosdhg where he Lves." Io other woids, he will be .ble to .cheve L@ooy ia hls so , also able to face the exirtinA problms, dd positivery feel the bappiness." lstqdrh is x chd"cter vhich oust be Lept by every fairhtul peoplc, 'tu md vonan, because with this charactc! a persd wifl bc able to kep the Is]anic tea.hinss wherEi he is.,",